Information Bulletin on New Methodologies Recommended for Adoption by Forensic Science Organizations of the Ministry of Justice of the Russian Federation - N. V. Mikhaleva (Теория и практика судебной экспертизы)
Issue 38 of the Information Bulletin presents summaries of methodologies published in 2015–2016 and recommended by the RFCFS Research Methodology Board for use by state forensic experts in their regular practice within the system of forensic science organizations of the Ministry of Justice. The Information Bulletin includes an overview of works published by RFCFS (including those that appeared in the journal "Theory and Practice of Forensic Science"), as well as by V.P. Serbsky Federal Medical Research Center for Psychiatry and Narcology of the Ministry of Health of the Russian Federation, and other organizations. Also included are descriptions of digital resources, manuals, and reference literature that may be of value to forensic practitioners. These materials may also be of interest to forensic examiners working at other public and private forensic science orgnizations, as well as investigators, judges, and lawyers.